Prognostic Value of Histopathological Features and Loss of H3K27me3 Immunolabeling in Anaplastic Meningioma: A Multicenter Retrospective Study - Gauchotte, Guillaume; Peyre, Matthieu; Pouget, Celso; Cazals-Hatem, Dominique; Polivka, Marc; Rech, Fabien; Varlet, Pascale; Loiseau, Hugues; Lacomme, Stéphanie; Mokhtari, Karima; Kalamarides, Michel; Bielle, Franck (Journal of neuropathology and experimental neurology, 2020)
Abstract The diagnosis of anaplastic meningioma (AM) (WHO grade III) is based on the presence of a high mitotic index (MI) and/or overt anaplasia. Only few data exist about the reproducibility and prognostic value of overt anaplasia. Additionally, the prognostic value of H3K27me3 loss in AM has not yet been demonstrated. Our objectives were to evaluate the reproducibility and prognostic value of WHO criteria and H3K27me3 loss in a multicenter series of 66 AM. Interobserver reproducibility was good for the determination of WHO grade (Kappa = 0.671) and MI (intraclass correlation coefficient [ICC] = 0.649), and fair for assessment of overt anaplasia (Kappa = 0.366). Patients with meningiomas showing high MI had significantly shorter overall survival (OS) than patients with meningiomas showing overt anaplasia without high MI (p = 0.009). OS was significantly lower in case of overt anaplasia with low MI (<20/1.6 mm2) than in atypical meningiomas (p = 0.008). H3K27me3 loss was present in 10/47 (21%) of AM and independently associated with shorter OS (p = 0.036; Cox multivariate analysis), with a good reproducibility (Kappa = 0.643). In conclusion, the presence of overt anaplasia could give additional prognostic information in tumors lacking high MI. Finally, loss of H3K27me3 is an easy-to-use and reproducible marker of poorer prognosis.